PEMANFAATAN DAN PELATIHAN PENGGUNAAN TEKNOLOGI INFORMASI DALAM PENGOLAHAN DATA INDUSTRI KULINER “ROSA CAKE” - Rezania Agramanisti Azdy; Febriyanti Darnis (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
Partners in the activities of the Stimulus Community Partnership Program (Program Kemitraan Masyarakat Stimulus/PKMS) is a home industry engaged in the culinary field, Rosa Cake. Rosa Cake offers products in the form of goods and services like ordering culinary products or organizing training in making food. The process of recording the order and registration of training in Rosa Cake is still done manually so that it is susceptible to data loss or damage in the recording which results in a decrease in the production process and the level of public confidence. This PKMS activity analyzes further the process of recording experienced by partners, as well as offering solutions by utilizing the use of information technology that is increasingly developing, especially in terms of system developers (developers). The data processed is the product order data and training registration organized by Rosa Cake. The research methods used adopting the system development methods that are commonly carried out, namely conducting socialization (needs analysis), system development (system design and manufacturing), training (as well as system testing), submission (sending the system to users), and evaluation (and maintenance). The results of this activity in the form of a system that can be a solution to the problem and in accordance with the needs of partners.